2011
DOI: 10.1093/annhyg/mer097
|View full text |Cite
|
Sign up to set email alerts
|

Use of the MEGA Exposure Database for the Validation of the Stoffenmanager Model

Abstract: The MEGA database could be used for model validation, although the presented analyses have learned that improvements in the database are necessary for modelling purposes in the future. For a substantial amount of data, contextual information on exposure determinants in addition to basic core information is stored in this database. The relative low bias, the good correlation, and the level of conservatism of the tested model show that the Stoffenmanager can be regarded as a useful Tier 1 model for the Registrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Modifications to these earlier versions have been made which are listed on (see under More, What is Stoffenmanager ® ). In the first step of the algorithm, a score is calculated as the sum of main exposure source near-field (NF; within 1 m of the worker’s head) and far-field (FF) and diffusive sources [21]. In the second step, a mixed-regression model based on calibration with experimental data is used to derive quantitative exposure estimates [22].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Modifications to these earlier versions have been made which are listed on (see under More, What is Stoffenmanager ® ). In the first step of the algorithm, a score is calculated as the sum of main exposure source near-field (NF; within 1 m of the worker’s head) and far-field (FF) and diffusive sources [21]. In the second step, a mixed-regression model based on calibration with experimental data is used to derive quantitative exposure estimates [22].…”
Section: Resultsmentioning
confidence: 99%
“…The lack of agreement was calculated between model estimates and measured concentrations by different authors [22,26,27]. The precision of the models was calculated by Koppisch et al [21], followed by Hornung [28], Schinkel et al [22], and Lee et al [27]. The aforementioned authors, Bekker et al [29], and Heussen and Hollander [25] also reported results regarding the bias of models, considering absolute and relative differences between estimates and measurements or, in the case of Heussen and Hollander [25], between STOFFENMANAGER ® and TREXMO estimates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These scores of various values were attributed regardless of the chemical dispersion process according to Cherrie et al [26]. The logarithmic scale is based on 'source-receptor' approach, of the conceptual model for inhalation exposure assessment [27]. From the emission source of the contaminants to the worker, through the exposure patterns, several modifying factors were identified.…”
Section: Task-level Assessment Methodsmentioning
confidence: 99%
“…5 indicates the barge loading operation and describes the task and identifies the source of vapor benzene emission location. The exposure predictive model used in this study has been validated from various studies such as those by Koppisch et al, [27], and Landberg et al, [28]. In order to estimate the benzene exposure concentration level at the Gabon's GSDF, the facility was divided into three main compartments with regards to breathing zones, i.e: We have ''near-field exposure'', ''far-field exposure'', and ''background exposure''.…”
Section: Task-level Assessment Methodsmentioning
confidence: 99%